2018
DOI: 10.12816/0043798
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Depression and Folate Deficiency

Abstract: Background: Folate is a naturally occurring B vitamin, is needed in the brain for the synthesis of norepinephrine, serotonin, and dopamine. Thus, previous researches suggested that folate levels play an important role in the etiology and course of depression. However, the literature has been inconsistent regarding differences in folate level between individuals with and without depression. The present metaanalysis synthesized the results of previous studies to examine whether individuals with depression had lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In addition to depression preventing effect, folate could enhance patient body response to the antidepressant medication. Studies suggest that 800 micrograms folic acid daily and 1 mg vitamin B12 daily could be tried to improve depression treatment outcomes [49,50].…”
Section: Folate and Vitamin B12mentioning
confidence: 99%
“…In addition to depression preventing effect, folate could enhance patient body response to the antidepressant medication. Studies suggest that 800 micrograms folic acid daily and 1 mg vitamin B12 daily could be tried to improve depression treatment outcomes [49,50].…”
Section: Folate and Vitamin B12mentioning
confidence: 99%
“…Folate or vitamin B9 is one of the water‐soluble vitamins that may play a role in depression (Lyon et al., 2020 ). Folate plays a fundamental role in maintaining one‐carbon metabolism for cell division and nucleic acid synthesis, regulation of gene expression, interconversion of amino acids and neurotransmitter synthesis, and neurological development during pregnancy and infancy (Gianfredi et al., 2022 ; Himayda et al., 2018 ; Hoepner et al., 2021 ; Jin et al., 2022 ; Xie et al., 2019 ; Yang et al., 2021 ). Growing research demonstrated that depression might be linked to folate deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies also showed that low‐serum folate levels have been positively associated with depression (Huang et al., 2018 ; Kaner et al., 2015 ; Khalili et al., 2022 ; Lin et al., 2020 ; Seppälä et al., 2013 ), whereas others have found no difference (Gargari et al., 2012 ; Gilbody et al., 2007 ; Kendrick et al., 2008 ). As a result, a substantial body of evidence suggests the introduction of supplemental folate in preventing and treating depression at the population and individual levels (Himayda et al., 2018 ). Figure 1 shows how folate could be related to depression.…”
Section: Introductionmentioning
confidence: 99%